Journalism reborn : the transformation of Chinese media in the mobile internet age - Yang, Chen, 1976- (London ; New York : Routledge, 2025)
"This book examines the strategies Chinese news media have implemented to address the challenges posed by the mobile Internet to Chinese journalistic practices and businesses. Using a variety of qualitative and quantitative research methods, the book analyzes the transformation of media convergence in China based on the characteristics of the mobile Internet. From three key perspectives - media organization, content, and users - the book discusses the difficulties Chinese journalism faces due to technological advances, and analyzes the evolving strategies of Chinese media and their implications. In doing so, the book provides a vivid picture of the transformation of Chinese journalism in the mobile Internet era and initiates a theoretical dialogue with global journalism studies. The title will appeal to scholars and students of journalism, news media, and communication, especially those interested in the case of China"--
Includes index.
Keywords: Journalism -- China; Online journalism -- China; Journalism -- Technological innovations -- China; Mass media policy -- China; SOCIAL SCIENCE / General; LANGUAGE ARTS & DISCIPLINES / Journalism; SOCIAL SCIENCE / Media Studies